1983
DOI: 10.1677/joe.0.0970113
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of ovarian follicles after inhibition of ovulation in rats

Abstract: The present investigation was performed to elucidate the mechanism of the initiation of follicular maturation after inhibition of ovulation in rats treated with pentobarbitone sodium at 13.30 h and progesterone at 14.00 h on the day of pro-oestrus (day 0 denotes the day of these treatments). Ovulation was completely inhibited and the next spontaneous ovulation occurred on day 5, the expected day of the next oestrus. Follicular responsiveness to injection of human chorionic gonadotrophin (hCG) indicated that pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
2
1
Order By: Relevance
“…This observation is not consistent with previous reports in cyclic rats, in which it was suggested that the periovulatory FSH surge in 4-or 5-day cyclic rats is responsible for follicular re¬ cruitment for the next oestrous cycle (Schwartz, 1974;Welschen & Dullaart, 1976;Sasamoto et al 1977: Hirshfield & Midgley, 1978aHoak & Schwartz, 1980;Hirshfield & DePaolo, 1981;Sasamoto et al 1981;Mizuno et al 1983). However, the development and maturation of Graafian follicles were observed during late pregnancy and lactation without an FSH surge (Richards & Kersey, 1979;Richards, 1980;Taya & Sasamoto, 1981).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This observation is not consistent with previous reports in cyclic rats, in which it was suggested that the periovulatory FSH surge in 4-or 5-day cyclic rats is responsible for follicular re¬ cruitment for the next oestrous cycle (Schwartz, 1974;Welschen & Dullaart, 1976;Sasamoto et al 1977: Hirshfield & Midgley, 1978aHoak & Schwartz, 1980;Hirshfield & DePaolo, 1981;Sasamoto et al 1981;Mizuno et al 1983). However, the development and maturation of Graafian follicles were observed during late pregnancy and lactation without an FSH surge (Richards & Kersey, 1979;Richards, 1980;Taya & Sasamoto, 1981).…”
Section: Discussioncontrasting
confidence: 99%
“…When ovulation is blocked by treatment with pentobarbitone and progesterone, the new wave of follicular maturation and the secretion of oestrogen, deduced from the pattern of changes in uterine weights (Mizuno et al 1983), appears to be similar to those observed in the present experiments. The presence of early atretic follicles on day 1 in rats treated with LHRH-AS or pentobarbi¬ tone and progesterone may exert an inhibitory effect on the initiation of new follicular maturation by inhi¬ biting FSH binding to granulosa cells through the local action of an FSH-binding inhibitor derived from the follicular fluid of large follicles (Darga & Reichert, 1978).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In normal rats, the ovaries secrete predominantly E 2 before ovulation and produce mainly progesterone after ovulation [17]. Mizuno et al [18] reported that ovulation in rats was delayed by 24 h by the administration of pentobarbital early in the afternoon of proestrus. We administered the anesthetics twice at 1 and 2 days to block ovulation completely.…”
Section: Discussionmentioning
confidence: 99%